Separation of the oil and protein fractions in coconut (Cocos nucifera Linn.) by fermentation - Puertollano, Carmen Luna 1935-; Kraus, Keith Stein (1969)
Various patented and unpublished methods of extracting oil from coconut meat by fermentation was studied and the best features were combined to devise a better process. Processing conditions were optimized wherever possible. The factors which must be controlled to break the emulsion and liberate the oil were investigated. It was found that coconut available commercially, which vary rather widely in maturity and length of storage before processing, varied in their response to fermentation processing. Approximately 50% of the milks produced from individual coconuts showed a breaking of the emulsion when fermented under controlled conditions. Forty per cent failed to break indicating that some factor(s) responsible for the coconut milk emulsion stability remained uncontrolled during fermentation. It was found that grinding conditions exerted a profound effect upon the stability of the coconut milk emulsion. The optimum condition for rapid fermentation of coconut milk and separation of the oil and protein was found to be 1:1 (w/v) coconut meat/water. Lactobacillus plantarum effected more rapid separation of oil then Lactobacillus delbrueckii. The fermentation progressed best under microaerophilic consitions at 40°C - 50°C. The fermentation was successful in breaking the emulsion at a relative broad ranges of pH and titrable acidity.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Coconut oil; Fermentation